The Garbhagriha of the Shiva Temple (Temple 3) - Temples of India Project Team (Jio Institute, 2024)
The garbhagriha (sanctum sanctorum) of the Shiva Temple (Temple 3) is a small square structure housing a Shiva linga at the centre. The rear wall is closed by a screen, which is also broken. The ceiling of the sanctum is also simple, featuring a square within a square.